High‐Performance Organic–Inorganic Hybrid Conductive Hydrogels for Stretchable Elastic All‐Hydrogel Supercapacitors and Flexible Self‐Powered Integrated Systems - Tao Cheng; Zhong‐Ting Liu; Jie Qu; Chao‐Fu Meng; Ling‐Jun He; Lang Li; Xuan‐Li Yang; Yu‐Jie Cao; Kai Han; Yi‐Zhou Zhang; Wen‐Yong Lai (Advanced Science)
Abstract Conductive polymer hydrogels exhibit unique electrical, electrochemical, and mechanical properties, making them highly competitive electrode materials for stretchable high‐capacity energy storage devices for cutting‐edge wearable electronics. However, it remains extremely challenging to simultaneously achieve large mechanical stretchability, high electrical conductivity, and excellent electrochemical properties in conductive polymer hydrogels because introducing soft insulating networks for improving stretchability inevitably deteriorates the connectivity of rigid conductive domain and decreases the conductivity and electrochemical activity. This work proposes a distinct confinement self‐assembly and multiple crosslinking strategy to develop a new type of organic–inorganic hybrid conductive hydrogels with biphase interpenetrating cross‐linked networks. The hydrogels simultaneously exhibit high conductivity (2000 S m−1), large stretchability (200%), and high electrochemical activity, outperforming existing conductive hydrogels. The inherent mechanisms for the unparalleled comprehensive performances are thoroughly investigated. Elastic all‐hydrogel supercapacitors are prepared based on the hydrogels, showing high specific capacitance (212.5 mF cm−2), excellent energy density (18.89 µWh cm−2), and large deformability. Moreover, flexible self‐powered luminescent integrated systems are constructed based on the supercapacitors, which can spontaneously shine anytime and anywhere without extra power. This work provides new insights and feasible avenues for developing high‐performance stretchable electrode materials and energy storage devices for wearable electronics.